Eutectic solidification processing : crystalline and glassy alloys - Elliott, Roy, Ph. D. (Butterworths monographs in materials., 1983)
Eutectic Solidification Processing: Crystalline and Glassy Alloys deals with solidification theory and its application to eutectic processing of crystalline and glassy alloys. The underlying theme is an analysis of the different paths taken by the liquid-solid transformation as the cooling rate increases and a description of the structure and properties of the solid formed, ranging from equilibrium to metastable phase formation in castings, to metallic glass formation in splat quenched ribbons. This text has seven chapters; the first of which describes the main characteristics of the liquid-so.